La "pertinaz sequía" en las cuencas hidrográficas del óvalo valenciano (1930-1960) - José Miguel Ruiz Pérez (Cuadernos de Geografía de la Universitat de València)
Episodes of climatological and hydrological drought are characterized in the Jucar Basin Council (between the rivers Serpis and Mijares) since 1930 to 1960, a crucial period for the hydrological planning and the development of flow regulation infrastructures. The episodes identified (1930-31, 1937- 39, 1944-45, 1948-50, 1952-55) affected in unequal degree to the territory. By its special socioeconomic incidence consequences of 1945?s drought are described, making reference to the repercussions on the electric supply.